Reconstructing Students’ Lorentz’s Force Conceptions by POE Tasks: Is It Effective? - Mufida, Shobrina Nurul; Asih, Tri Lestari Budi; Elfiana, Dwi Endah; Agustin, Putri Nanda; Samsudin, Achmad; Umar, Fini Alfionita (Spectrum of Science Education Research and Application, 2024)
Students' conceptions regarding Lorentz’s force do not always fit scientific conceptions after learning in class. Alternative learning that can be done is supported by relevant tasks. Therefore, this research aims to describe the development and effectiveness of POE (Predict-Observe-Explain) Tasks in reconstructing students' conceptions of Lorentz Forces on straight wires. The 3D+1I (Defining, Designing, Developing, and Implementing) research design was used in this research. In the development stage, researchers added practical activities on Observe (O) step, namely using LoFoPaT (Lorentz Force Practicum Tools). The implementation stage was given to 20 high school students (9 boys and 11 girls, with an average age of 17 years) at one of the schools in Tuban, East Java, Indonesia. After being tested using the Four-Tier Instrument on Lorentz’s Force (FILOF) for the pre-post test, the results obtained were an N-Change value of 0.73 in the "High Effect" category. Most of the changes occurred in the Acceptable Change category from No Understanding (NU), Misconceptions (MC), Partial Negative (PN) to Sound Understanding (SU) or Partial Positive (PP). Eventually, this research can conclude that the POE Tasks were successfully developed and can be used to reconstruct students' conceptions into scientific conceptions based on Lorentz’s force concepts